Editorial Board Thoughts: Content and Functionality–Know When to Buy ’Em, Know When to Code ’Em - Varnum, Kenneth J. (Information Technology and Libraries, 2017)
Editorial Board Thoughts: Content and Functionality–Know When to Buy 'Em, Know When to Code 'Em